1988
DOI: 10.1073/pnas.85.18.6968
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 has an additional coding sequence in the central region of the genome.

Abstract: Eight coding regions designated gag,pol, env, sor, R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 42 publications
0
33
0
1
Order By: Relevance
“…§1734 solely to indicate this fact. 3 and then centrifuged at 35,000 ϫ g for 30 min. The resulting pellet was sonicated twice for 4 min on ice in binding buffer (6 M guanidine hydrochloride͞5 mM imidazole͞0.5 M NaCl͞20 mM Tris-Cl, pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…§1734 solely to indicate this fact. 3 and then centrifuged at 35,000 ϫ g for 30 min. The resulting pellet was sonicated twice for 4 min on ice in binding buffer (6 M guanidine hydrochloride͞5 mM imidazole͞0.5 M NaCl͞20 mM Tris-Cl, pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…Vpu, one of four accessory proteins encoded in the HIV-1 genome, is an 81-residue membrane protein (1)(2)(3). A growing body of evidence from biological, functional, and structural studies indicates that its two principal biological activities are associated with different structural domains of the protein (4).…”
mentioning
confidence: 99%
“…[1][2][3] Studies in a macaque model have shown that Vpu from subtype B plays a crucial role in massive loss of circulating CD4 ϩ T lymphocytes, 4-6 which can be modulated by replacing it with Vpu from subtype C. 7 The exact mechanism(s) underlying how Vpu makes HIV-1 more pathogenic is only partially understood. 8,9 Vpu is involved in ubiquitination and degradation of antiretroviral restriction factor BM stromal cell Ag 2 (BST-2; also known as tetherin) and surface receptor CD4 through their recruitment to SCF ␤-TrcP (Skp1/Cul1/F-box) ubiquitin ligase (SCF) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the typical retroviral gag, pol, and env genes, HIV encodes a series of accessory genes, vif, vpr, vpx, vpu, and ne$ The vpu gene is found exclusively in HIV-1 (Strebel et al, 1988;Cohen et al, 1988;Matsuda, 1988). In tissue culture systems, defects in accessory genes are frequently not correlated with a detectable impairment of virus replication and, as a result, these genes are often referred to as "non-essential".…”
Section: Introductionmentioning
confidence: 99%